Application of Generalized Failure Mechanism Knowledge to Reprocessing Plant for Supporting Maintenance Activity - YASUDA, Yuuya; TAKAHASHI, Makoto (Nihon Genshiryoku Gakkai wabun ronbunshi = Transactions of the Atomic Energy Society of Japan, 2022)
To achieve a higher level of safety in the Rokkasho reprocessing plant, it is important to predict the failure mechanism extensively and proactively. Although the effort toward such proactive approaches to explore the possibility of potential failure mechanisms has been based mainly on human experience, the possibility of overlooking important failure mechanisms should be decreased as much as possible. In the present study, the concept of Generalized Failure Mechanism Knowledge (GFMK) has been practically applied to the Rokkasho reprocessing plant, and the applicability of the proposed method to the maintenance activities has been evaluated. GFMK is a knowledge scheme that describes failure mechanisms independent of any particular subject. In this scheme, specific conditions are generalized, which allows us to apply GFMK to completely different equipment. The GFMK base has been built from the records of trouble at the Rokkasho reprocessing plant and applied to the SFP cooling pump to derive possible failure modes, and its appropriateness has been confirmed. As one of the derived failure mechanisms has not been considered in the maintenance activities, the authors believe that the proposed method may contribute to avoiding overlooking possible failures.